Enhanced Antioxidant Activity under Biomimetic Settings of Ascorbic Acid Included in Halloysite Nanotubes - Andrea Baschieri; Riccardo Amorati; Tiziana Benelli; Laura Mazzocchetti; Emanuele D'Angelo; Luca Valgimigli (MDPI AG, 2019)
Antioxidant activity of native vitamin C (ascorbic acid, AH2) is hampered by instability in solution. Selective loading of AH2 into the inner lumen of natural halloysite nanotubes (HNT) yields a composite nanoantioxidant (HNT/AH2), which was characterized and investigated for its reactivity with the persistent 1,1-diphenyl-2-picrylhydrazyl (DPPH•) radical and with transient peroxyl radicals in the inhibited autoxidation of organic substrates, both in organic solution (acetonitrile) and in buffered (pH 7.4) water in comparison with native AH2. HNT/AH2 showed excellent antioxidant performance being more effective than native ascorbic acid by 131% in acetonitrile and 290% (three-fold) in aqueous solution, under identical settings. Reaction with peroxyl radicals has a rate constant of 1.4 × 106 M−1 s−1 and 5.1 × 104 M−1 s−1, respectively, in buffered water (pH 7.4) and acetonitrile, at 30 °C. Results offer physical understanding of the factors governing HNT/AH2 reactivity. Improved performance of HNT/AH2 is unprecedented among forms of stabilized ascorbic acid and its relevance is discussed on kinetic grounds.